Grammatical aspects of the moves in popular scientific reports - Stejskalová, Tereza (Univerzita Pardubice, 2012)
An attempt made in this work is to define the grammatical aspects of the moves in the generic structure of popular scientific reports (PSRs). The basic aspects contained in the theoretical part are move analysis; the process of science popularization, a definition of PSRs and the modified structure of PSRs. In the practical part 35 popularised reports randomly chosen in internet were examined in detail using the modified structure based on the Nwogu's structure (1991). The results obtained from this analysis indicate that PSRs have a schema made up of eight schematic structures called "moves". Each move fulfils a particular purpose and contains the grammatical features typical to it. In this work, a grammatical feature refers to the most frequent grammatical aspect occurring in a concrete move. The occurrence as well as the function of each grammatical feature is always associated with the purpose of a concrete move and sometimes also with the lexical signals of a particular move.
Gramatické aspekty ve struktuře populárně vědeckých prací
Keywords: populárně naučné zprávy; gramatické jevy; move analysis; science popularization; generic structure of PSRs; grammatical features